1984
DOI: 10.1136/gut.25.7.748
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early neoplastic changes in experimentally induced colorectal cancer using scanning electron microscopy and cell kinetic studies.

Abstract: SUMMARY Colonic tumours were induced in Wistar rats using 12 consecutive subcutaneous injections of azoxymethane at a dose of 10 mg/kg/week. Pairs of rats were killed at five weekly intervals after initial injection until 25 weeks. Colonic mucosa was sampled from five standard areas along the length of the colon and examined by both scanning electron microscopy and conventional light microscopy. The crypt cell production rate was measured by stathmokinetic techniques. Scanning electron microscopy showed microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…In our study, the colonic CCPRs of the groups treated with rectally administered saline were similar to previously reported values in both the carcinogen treated and control animals (Cooke et al, 1984). The stimulatory effect of the carcinogen was not seen at the 10 cm position in this study; indeed, azoxymethane is known to produce a range of responses throughout the colon (Cooke et al, 1984).…”
Section: Animalssupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the colonic CCPRs of the groups treated with rectally administered saline were similar to previously reported values in both the carcinogen treated and control animals (Cooke et al, 1984). The stimulatory effect of the carcinogen was not seen at the 10 cm position in this study; indeed, azoxymethane is known to produce a range of responses throughout the colon (Cooke et al, 1984).…”
Section: Animalssupporting
confidence: 91%
“…The stimulatory effect of the carcinogen was not seen at the 10 cm position in this study; indeed, azoxymethane is known to produce a range of responses throughout the colon (Cooke et al, 1984). The higher dose of EGF caused a significant stimulation of mucosal growth at the 5 cm sampling site in the control animals when compared to the animals receiving the lower dose.…”
Section: Animalsmentioning
confidence: 47%
“…Using the same animal model, we have found that during carcinogenesis there is an increase in the crypt cell production rate in the descending colon (Cooke et al, 1984). This leads to an increase in the size of the proliferative compartment and to an increase in the mean cellular DNA content in the middle of the crypts.…”
Section: Cell Kineticsmentioning
confidence: 76%
“…In adenomas, which in this model are believed to be premalignant lesions (Cooke et al, 1984), the mean cellular DNA levels are the same throughout the length of the crypts indicating that all of these cells have the same reproductive capacity. It is also possible that some of these polyps are composed of clones of aneuploid cells.…”
Section: Cell Kineticsmentioning
confidence: 94%
See 1 more Smart Citation